2019
DOI: 10.3390/medsci7070081
|View full text |Cite
|
Sign up to set email alerts
|

Dream Recall and Content versus the Menstrual Cycle: A Cross-Sectional Study in Healthy Women

Abstract: The association between sleep and the menstrual cycle has been scarcely studied. This study aimed to investigate the association between dream recall and content and the menstrual cycle among a large sample of young women. To this aim, 944 women were asked about their day of menstrual cycle, whether they remembered the previous night’s dreams and if they did so to describe the dream content as pleasant or unpleasant. A total of 378 women recalled the previous nights’ dreams, with 199 reporting pleasant dream a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In a study of 944 women with normal menstrual cycles, an association of pleasant dream content with the luteal phase was reported. We suggest that F in the luteal phase may selectively enhance dream amnesia, easing the recall of pleasant dreams [35].…”
Section: Dream Recall and The Hpa Axismentioning
confidence: 86%
“…In a study of 944 women with normal menstrual cycles, an association of pleasant dream content with the luteal phase was reported. We suggest that F in the luteal phase may selectively enhance dream amnesia, easing the recall of pleasant dreams [35].…”
Section: Dream Recall and The Hpa Axismentioning
confidence: 86%
“…The results of previous studies regarding this subject have been conflicting [ 22 , 23 ]. In a previous study of ours, we showed that, during the luteal phase of the menstrual cycle, women reported pleasant dreams more frequently [ 19 ]. However, the sample size of the present study was limited, and thus our results could not be replicated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients with post-traumatic stress disorder (PTSD), who suffer from frequent nightmares, are characterized by decreased cortisol levels compared to healthy subjects [ 6 ]. In a previous study of ours, women reported more frequently pleasant dreams during the luteal phase of the menstrual cycle, where cortisol levels are slightly lower compared to the follicular phase [ 19 ].…”
Section: Introductionmentioning
confidence: 99%